How to use artificial inteligence to generate teaching materials, such as study guidelines and multimedia resources - Avilés Carias, Carlos Enrique; Batres Zelada, Jimmy Stanley; Carías Pineda, Nilya Dorin (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2025)
Disponible en soporte impreso